2001
DOI: 10.1183/09031936.01.00209301
|View full text |Cite
|
Sign up to set email alerts
|

Controlled, prospective trial of psychosocial function before and after continuous positive airway pressure therapy

Abstract: The aim of the study was to investigate psychosocial function before and after continuous positive airway pressure (CPAP) therapy, and establish the determinants and consequences of objective CPAP use.In a prospective, parallel-group study, changes in psychosocial scores were compared with conservative management or CPAP therapy for the sleep apnoea/hypopnoea syndrome (SAHS). Patient/partner couples from the top (CPAP treated, n=44) or bottom (conservatively treated, n=25) of a CPAP waiting list rated marital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 31 publications
2
41
0
1
Order By: Relevance
“…Other studies report no effect of ESS score prior to treatment on determining CPAP compliance [13,33]. However, studies assessing changes in patient perceptions following treatment initiation have found that an improved ESS score often predicts current CPAP use [9,17,31]. Thus, the present study supports research suggesting that initial ESS score, along with many other biomedical indices of disease severity, are inconsistent early predictors of CPAP adherence.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Other studies report no effect of ESS score prior to treatment on determining CPAP compliance [13,33]. However, studies assessing changes in patient perceptions following treatment initiation have found that an improved ESS score often predicts current CPAP use [9,17,31]. Thus, the present study supports research suggesting that initial ESS score, along with many other biomedical indices of disease severity, are inconsistent early predictors of CPAP adherence.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies have begun to investigate the utility of psychological models in the prediction of CPAP acceptance and subsequent adherence [13,[15][16][17][18][19]. Patients begin to develop expectations and beliefs regarding OSA and CPAP treatment even before taking the treatment home [20].…”
mentioning
confidence: 99%
“…Sleep medicine professionals are focused on encouraging greater PAP use and no doubt incorporate naturalistic approaches aligned with patients' learning curves, but adherence rules may interfere with this general practice model of care for select patients. In the real world, given that PAP benefits accrue during a variable time line, 60 like so many medications, the concept of use may provide a more pragmatic clinical tool in patient management, and speculatively, a use framework may ultimately lead to greater compliance.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite wellfounded impact of CPAP treatment on the quality of life of the patients, there is still little understanding regarding the significance of these changes in emotional functioning of their spouses. The most frequent symptoms of OSAHS patients-daytime sleepiness, fatigue, and cognitive impairment-may not only limit patients' everyday functioning, but also undermine their relations with the family [15,17]. Our study emphasizes the possible reciprocity between the changes in the emotional well-being of patients and their bed partners.…”
Section: Discussionmentioning
confidence: 62%